A review on prevalence and antimicrobial resistance in salmonella enteritidis and salmonella typhimurium in poultry - Tasnim, Kazi Jannatul (Brac University, 2024)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Microbiology, 2023.